Monday
March 27, 2017

Post a New Question

Posted by on .

((k^2+6k+9)/(k^2+12k+27))×(k^2+9)/((k^2+12k+27))
express in lowest terms

  • Algebra - ,

    k ^ 2 + 6 k + 9 = ( x + 3 ) * ( x + 3 )



    k ^ 2 + 12 k + 27 = ( x + 9 ) * ( x + 3 )


    ((k^2+6k+9)/(k+9)*(k+3)))*(k^2+9)/((k^2+12k+27))=

    ((k+3)*(k+3))/((x+9)*(k+3)) * ((k^2+9)/(((x+9)*(k+3))=

    ((k+3))/((x+9)) * ((k^2+9)/(((x+9)*(k+3))=

    (k^2+9)/((x+9)*(k+9))=

    (k^2+9)/(x+9)^2

  • Algebra - ,

    (k^2+9)/((k+9)*(k+9))=

    (k^2+9)/(k+9)^

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question